2016
DOI: 10.1155/2016/5780538
|View full text |Cite
|
Sign up to set email alerts
|

Detection of OSR2, VAV3, and PPFIA3 Methylation in the Serum of Patients with Gastric Cancer

Abstract: Aim. This study was to evaluate the diagnostic value of OSR2, VAV3, and PPFIA3 hypermethylation in gastric cancer (GC) patients. Patients and Methods. By using methylation-specific polymerase chain reaction (MSP), we detected the methylation status in tissue and serum samples from 48 gastric cancer (GC) patients and 25 normal individuals. Results. We found that OSR2, VAV3, and PPFIA3 were methylated in 70.8% (34/48), 54.2% (26/48), and 60.4% (29/48) of GC tissue, respectively. On the contrary, those genes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Several molecular detection methods, such as methylation-specific PCR (MSP) or quantitative MSP (qMSP), were applied in enrolled studies. One study [ 15 ] used bisulfite genomic sequence and another [ 23 ] used Taqman PCR to measure the status of specific circulating DNA in GC patients. The blood volume used for DNA detection varied between 400 ul–5 ml with a median volume of 1.5ml.…”
Section: Resultsmentioning
confidence: 99%
“…Several molecular detection methods, such as methylation-specific PCR (MSP) or quantitative MSP (qMSP), were applied in enrolled studies. One study [ 15 ] used bisulfite genomic sequence and another [ 23 ] used Taqman PCR to measure the status of specific circulating DNA in GC patients. The blood volume used for DNA detection varied between 400 ul–5 ml with a median volume of 1.5ml.…”
Section: Resultsmentioning
confidence: 99%
“…A study on whole-exome sequencing identified that PTPN12 variant is associated with CRC susceptibility [46]. In addition, the methylation of PTPRF-interacting protein alpha 3(PPFIA3) in serum has shown a potential for the detection of gastric cancer [47].…”
Section: Discussionmentioning
confidence: 99%
“…A study on whole-exome sequencing identi ed that PTPN12 variant is associated with CRC susceptibility (46). In addition, the methylation of PTPRF-interacting protein alpha 3(PPFIA3) in serum has shown a potential for the detection of gastric cancer (47).…”
Section: Discussionmentioning
confidence: 99%